Methods for demonstrating a competence and criteria for evaluating a competence in STCW Convention - Gundić, Ana (Array, 2020)
STCW Convention has defined competences needed for jobs onboard, methods for demonstrating competences and criteria for their evaluation. Every MET institution has to include minimal standards, prescribed by STCW Convention, in programmes for seafarers they have been carrying out. Apart from the obligatory STCW regulations, every institution carrying out STCW Convention based programme can include IMO Model Courses in the programme as well. In STCW Convention, competences and methods for their demonstration as well as criteria for their evaluation have been divided on the basis of ship’s departments. The paper is about standards that refer to deck department. Methods for demonstrating competences and criteria for their evaluation defined by STCW Convention, and the ones defined by IMO Model Courses were compared. They depend on well-defined learning outcomes. In order to determine whether learning outcomes, defined by both, STCW Convention and IMO Model Courses, are in accordance with Bloom’s Taxonomy, a lexical analysis for STCW A-II/1, column 2, A-II/2, column 2, Model Course 7.01 – Part C and Model Course 7.03 – Part C was done. Software Wordsmith 7.0, produced and delivered by Lexical Analysis Software and Oxford University press, was used in the research. The results of the research show that methods for demonstrating competences and criteria for their evaluation have not been written clearly enough. It was found out that methods for demonstrating competences and criteria for their evaluation defined by STCW Convention are not in accordance with Bloom’s Taxonomy and commonly used methods and criteria. On the other hand, they are defined precisely in IMO Model Courses. Furthermore, there still exists a problem of IMO Model Courses being non-mandatory.